2020
DOI: 10.1108/jeas-04-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

Stock market performance: is the weather a bother in the tropics? Evidence from Ghana

Abstract: PurposeIn the wake of climate change and its associated impact on firms' performance, this paper attempts to provide a piece of empirical evidence in support of the effect of weather conditions on the stock market performance.Design/methodology/approachMonthly time-series dataset and the fully modified ordinary least square (FMOLS) semi-parametric econometric technique are used to establish the effect of weather variables on stock market return.FindingsThis study finds that temperature and wind speed have a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…The dependent variable is chosen because in empirical literature (see [ 23 , 38 , 50 ]) stock market performance has been measured using the stock market index. Similarly, in this study we used stock market index as a measure of stock market performance as our dependent variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable is chosen because in empirical literature (see [ 23 , 38 , 50 ]) stock market performance has been measured using the stock market index. Similarly, in this study we used stock market index as a measure of stock market performance as our dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Al-Awadhi et al . [4] and Li [36] have noted that returns on the stock market respond to major events such as disasters (Kowalewski & Spiewanowski, 2020), news [37] and weather [50] and political events [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Kpanie et al (2014) also identified a significant long-run relationship between the Ghana Stock Exchange's performance and oil prices and money supply in Ghana. Tetteh & Amoah (2020) found that temperature, wind speed, and humidity has adverse effect on stock market performance in Ghana. Market players must therefore be very considerate of the various seasonal changes in the weather as they have a significant impact on investor behaviors and the performance of the Journal of Financial Risk Management stock markets.…”
Section: Introductionmentioning
confidence: 99%